2007
DOI: 10.1002/mar.20185
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of gambling motivations and their impact on the purchase frequencies of various gambling products

Abstract: The global gambling industry is huge and gambling has become a leading leisure activity in many countries. Although research on gambling is extensive, many gaps remain. The objective of this exploratory study was to examine how motivations for regular gambling varied by the forms of game played. Using data collected by the U.S. National Gambling Impact Study Commission, the study found that regular gamblers were motivated to gamble to win and to fulfill their sense of excitement/challenge for some gambling pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 26 publications
1
38
0
1
Order By: Relevance
“…A study of 1500 adult social gamers from the US found that 46% of social gamers said that playing with friends is the most important feature to them (Shaul, 2013). In comparison, gambling is typically motivated by winning, although socialisation is an important factor for some gamblers (Custer & Milt, 1985;Lam, 2007;McBride & Derevensky, 2009). Further research should examine the motivations of social casino gamers and what leads them to choose to play gambling or social casino games at different times.…”
Section: Social Casino Gamersmentioning
confidence: 99%
“…A study of 1500 adult social gamers from the US found that 46% of social gamers said that playing with friends is the most important feature to them (Shaul, 2013). In comparison, gambling is typically motivated by winning, although socialisation is an important factor for some gamblers (Custer & Milt, 1985;Lam, 2007;McBride & Derevensky, 2009). Further research should examine the motivations of social casino gamers and what leads them to choose to play gambling or social casino games at different times.…”
Section: Social Casino Gamersmentioning
confidence: 99%
“…Control variables were considered along with level of gambling participation for each type of gambling (dependent variable). Previous studies found that gambling level is associated with age (Burns, Gillet, Rubinstein, & Gentry, 1990;Herring & Bledsoe, 1994;Young & Stevens, 2009), education level (Lam, 2007;Rogers, 1998), and income (Abbot & Cramer, 1993;Currie et al, 2006). We also tested for multicollinearity among independent variables and found that variance inflation factors ranged from 1.006 to 1.422, which are within the acceptable range (see O'brien, 2007).…”
Section: Methodsmentioning
confidence: 77%
“…Gambling, in the case of casino participation, is conducted indoors within a comfortable environment. In particular, activities involving a casino typically require individuals to physically go to a specific venue (e.g., casino or related gaming centre) and thus may be substitutes for other social, leisure, or sports activities (Lam, 2007). Hence, gambling may be an attractive choice for obese individuals, similar to the relationship between a sedentary lifestyle and obesity, especially TV watching (Johnson- Taylor & Everhart, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Individualism sponsors self-fulfillment and satisfaction, which includes the pursuit of fame and wealth. Gambling to win has always been one of the major explanations for continued gambling, often ranked within the top three gambling motivations (Lam, 2007). Thus, high individualism may in some ways relate to average gambling expenditure per person.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps one explanation is that, unlike casino gambling, lottery is an individual game. Lam (2007), who investigated gambling motivations for nine different forms of games, found that social factor was not a significant motivator for lottery purchase. Whether it is in an individualistic or collectivistic culture, the factors (internal and external) that influence lottery purchase are perhaps similar.…”
Section: Discussionmentioning
confidence: 99%